The Effect of Soymilk by Product Supplemented in the Ration on Growth Performance of Male Broiler Chicken - Indarto, Edwin; Zuprizal, Zuprizal; Kustantinah, Kustantinah; Jamhari, Jamhari; Zahra, F (2012)
An experiment was conducted to find out the effect of use of Dried Distillers Grain with Soluble (DDGS) with low energy diet on carcass, abdomen fat and liver of broiler throughout 35 days growing period. This experiment was conducted using 125 one day old chicks. The birds were randomly devided into five dietary treatments. Each dietary treatment was assigned to five replicate pens of five chicks. Diets were contain of 0, 20, 30, 40 and 50% DDGS. At 35-days old, 25 birds were weighted and slaughtered, then the carcass, abdomen fat and liver were weighted. This experiment used the Complete Randomized Design (CRD) and the data were analyzed by Oneway Anova. The Duncan's New Multiple Range Test(DMRT) used if there were the significant differences. There were significant effects of DDGS level on carcass weight and percentage, abdomen fat and percentage, and liver weight. Carcass weight of broiler chicken of R 0, R 20, R 30, R 40 and R 50 were 625.40 ± 55.38, 608.60 ± 55.61, 568.20 ± 123.87, 422.80 =55.97 and 401.80 = 47.53, respectively, carcass percentage were 61.79 + .83, 61.70 ± 2.78, 60.17 f 2.57, 57.19 ± 2.22 and 56.68=3.61%, respectively, abdomen fat weight were 15.60=3.28. 15 00 + 4.00, 13.20 = 5.63, 5.60 ± 3.28 and 4.20 = 2.86 gram, respectively, abdomen fat percentage were 1.56 + 0.42, 1.53 + 0.46, 1.37 ± 0.46, 0.77 ± 0.47, and 0.61 ± 0.42%. respectively, and liver weight were 22.20 ± 2.94, 21.80 = 3.96, 20.80 ± 0.39, 15.80 ± 2.77and 15.80 + 1.92 gram. Conclusion the use of DDGS up to 30% level could maintain the carcass, but the use of 40% DDGS level decreased carcass weight and percentage, as well as the abdomen fat and liver.